2011
DOI: 10.1016/j.anr.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Experience and Perception of Sexual Harassment During the Clinical Practice of Korean Nursing Students

Abstract: Education program is needed to prevent sexual harassment and enhance the gender sensitivity of nursing students, who are in the high-risk group of sexual harassment during clinical practice. This will in turn contribute to a safe educational environment for clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 20 publications
9
55
0
1
Order By: Relevance
“…Sexual harassment has been described as any unwelcome sexual advances, requests for sexual favours or other physical and expressive behaviour of a sexual nature (Aluede, 2000). It has also been described as repeated and unwelcome sexual comments, looks, or physical contact at workplaces or other places, and is related to not only sexuality but Sexual harassment has been reported in both work places and educational institutions (Menon et al, 2009) also uneven power (Lee et al, 2011;Chen et al, 2009). and it interferes with prevalence rates of 13.8% (Kullima et al, 2010) and human Human rights (Sigal, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual harassment has been described as any unwelcome sexual advances, requests for sexual favours or other physical and expressive behaviour of a sexual nature (Aluede, 2000). It has also been described as repeated and unwelcome sexual comments, looks, or physical contact at workplaces or other places, and is related to not only sexuality but Sexual harassment has been reported in both work places and educational institutions (Menon et al, 2009) also uneven power (Lee et al, 2011;Chen et al, 2009). and it interferes with prevalence rates of 13.8% (Kullima et al, 2010) and human Human rights (Sigal, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies from educational institutions in Nigeria had reported range from 67 to 99% on various forms of sexual harassment (Imonikhe et al, 2012). Nursing profession has been reported to have the possibility of sexual harassment and sexual discrimination in the medical field because most workers in nursing are still women (Lee et al, 2011). Sexual harassment in the nursing profession was first reported/observed during Crimean War where drunken non-commissioned officers; male porters loitering in hospital stairwells made themselves objectionable to student nurses as well as maltreatment by male physicians and surgeons (Kaye, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sexual harassment in the healthcare industry, as a whole, has been prevailing for decades that affect a wide range of medical practitioners. For instance, Lee, Song, and Kim (2011) posited that over 52 percent of 542 female Korean nursing students had experienced at least one type of sexual harassment during their clinical practice. The perpetrators are mostly male patients in their 40s with whereby the majority of them are in the psychiatric ward.…”
Section: An Overview Of Sexual Harassment On Medical Practitioners Inmentioning
confidence: 99%
“…Moreover, these stakeholders should also be informed about their rights through various means. For instance, training for employees should be conducted on a timely basis (Lee et al, 2011) instead of being treated as an annual program because methods of exposure and training frequency are the elements for useful sexual harassment training outcome.…”
Section: Strategies For Precautionary and Corrective Actions To Sexuamentioning
confidence: 99%
“…. 국내 간호학과 학생들을 대상으로 한 선행연구에 서도 응답자의 50% 이상이 임상실습 중 적어도 한 번 이상의 성희 롱 피해를 입었다고 하였다 [10,11]. 의료현장에서 성희롱과 같은 폭 력을 경험한 대상자들은 극도의 스트레스와 자존감 손상 및 모욕 감 등의 부정적 정서를 갖게 된다고 하였다 [12,13].…”
unclassified